Evaluation of surgical resection in advanced ovarian, fallopian tube, and primary peritoneal cancer: laparoscopic assessment. A European Network of Gynaecological Oncology Trial (ENGOT) group survey. Issue 6 (June 2020) - Greggi, Stefano; Falcone, Francesca; Scaffa, Cono; du Bois, Andreas; Samartzis, Eleftherios Pierre Pierre; Pujade‐Lauraine, Eric; Cibula, David; Mądry, Radoslaw; Korach, Jacob; Gungorduk, Kemal; McNeish, Iain A; Zanagnolo, Vanna; et al.
ABSTRACT : Objective : Laparoscopy is one of the diagnostic tools available for the complex clinical decision‐making process in advanced ovarian, fallopian tube, and peritoneal carcinoma. This article presents the results of a survey conducted within the European Network of Gynaecological Oncology Trial (ENGOT) group aimed at reviewing the current patterns of practice at gynecologic oncology centers with regard to the evaluation of resection in advanced ovarian, fallopian tube, and peritoneal carcinoma. Methods : A 24‐item questionnaire was sent to the chair of the 20 cooperative groups that are currently part of the ENGOT group, and forwarded to the members within each group. Results : A total of 142 questionnaires were returned. Only 39 respondents (27.5%) reported using some form of clinical (not operative) score for the evaluation of resection. The frequency of use of diagnostic laparoscopy to assess disease status and feasibility of resection was as follows: never, 21 centers (15%); only in select cases, 83 centers (58.5%); and routinely, 36 centers (25.4%). When laparoscopy was performed, 64% of users declared they made the decision to proceed with maximal effort cytoreductive surgery based on their personal/staff opinion, and 36% based on a laparoscopic score. To the question of whether laparoscopy should be considered the gold standard in the evaluation of resection, 71 respondents (50%) answered no, 66 respondents (46.5%) answered yes, whereas 5 respondents (3.5%) did not provide an answer. Conclusions : This study found that laparoscopy was routinely performed to assess feasibility of cytoreduction in only 25.4% of centers in Europe. However, it was commonly used to select patients and in a minority of centers it was never used. When laparoscopy was adopted, the treatment strategy was based on laparoscopic scores only in a minority of centers.